Shorelands - Gaba, Marc 1978- (Manila University of Santo Tomas Publishing House, 2015)
"A first in Philippine literature, Marc Gaba's shorelands is built with lines form the first English translation of El Filibusterismo. Using the Oulipian constrained writing method first developed in 1960s France, Shorelands contributes to a new understanding of literature, nationalist agendas, and the current materiality of culture."--Back cover.
On : a prologue -- On -- Tales -- Basilio -- O -- Placid -- Past -- Juli -- On : an epilogue -- Tange : an afterword -- Notes.
Keywords: Philippnine poetry (English); Philippnine poetry (English) -- Collections